Role of Taxes Save The Business Affected by Covid 19 Pandemi in Indonesia - Maharani Chikita Angelina; Antin Okfitasari; Lyly Katniaty; Safitri Nur (LPPM Universitas Duta Bangsa Surakarta, 2021)
The purpose of this study is to analyze the role of taxes during the covid 19 pandemic. The research method used is qualitative research using a literature approach. This research describes the role of taxes during the Covid-19 pandemic. The result of this research is that fiscal policy has changed its function from budgetary to regular-end in order to save the economy in Indonesia. Taxes also function as stability in financing all areas affected by the pandemic. It is undeniable that covid 19’s handling are fully financed by state revenue from the tax income. For this reason, supervision of the use of covid 19’s handling funds must be monitored, so that there are no wrong targets. Tax incentives are also provided to taxpayers as a way to reduce the economic impact on their business due to the pandemic. In this case, the tax sacrifices all existing policies in order to ease the Indonesian people who are currently affected by the pandemic. With all the tax relaxation, it is hoped that the business world of Indonesia will continue to survive and even grow the midst of the ongoing pandemic, so that the Indonesian economy will also grow.